Question and Answers Forum

All Questions      Topic List

Limits Questions

Previous in All Question      Next in All Question      

Previous in Limits      Next in Limits      

Question Number 100134 by bemath last updated on 25/Jun/20

lim_(x→(π/2))  ((4sin x−(√(6(√(sin x))+10)))/((π/2)−x)) ?

$$\underset{{x}\rightarrow\frac{\pi}{\mathrm{2}}} {\mathrm{lim}}\:\frac{\mathrm{4sin}\:\mathrm{x}−\sqrt{\mathrm{6}\sqrt{\mathrm{sin}\:\mathrm{x}}+\mathrm{10}}}{\frac{\pi}{\mathrm{2}}−\mathrm{x}}\:? \\ $$

Commented by bobhans last updated on 25/Jun/20

set (π/2)−x = t , x =(π/2)−t   lim_(t→0)  ((4cos t−(√(6(√(cos t))+10)))/t) =  lim_(t→0)  ((16cos^2 t−(6(√(cos t))+10))/(8t)) =  lim_(t→0) ((−16sin 2t−((6(−sin t))/(2(√(cos t)))))/8) = 0

$$\mathrm{set}\:\frac{\pi}{\mathrm{2}}−\mathrm{x}\:=\:\mathrm{t}\:,\:\mathrm{x}\:=\frac{\pi}{\mathrm{2}}−\mathrm{t}\: \\ $$$$\underset{\mathrm{t}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{\mathrm{4cos}\:\mathrm{t}−\sqrt{\mathrm{6}\sqrt{\mathrm{cos}\:\mathrm{t}}+\mathrm{10}}}{\mathrm{t}}\:= \\ $$$$\underset{\mathrm{t}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{\mathrm{16cos}\:^{\mathrm{2}} \mathrm{t}−\left(\mathrm{6}\sqrt{\mathrm{cos}\:\mathrm{t}}+\mathrm{10}\right)}{\mathrm{8t}}\:= \\ $$$$\underset{\mathrm{t}\rightarrow\mathrm{0}} {\mathrm{lim}}\frac{−\mathrm{16sin}\:\mathrm{2t}−\frac{\mathrm{6}\left(−\mathrm{sin}\:\mathrm{t}\right)}{\mathrm{2}\sqrt{\mathrm{cos}\:\mathrm{t}}}}{\mathrm{8}}\:=\:\mathrm{0} \\ $$$$ \\ $$

Commented by Dwaipayan Shikari last updated on 25/Jun/20

lim_(x→(π/2)) ((−4cosx−(((1/2).(3/(√(sinx)))cosx)/(√(6(√(sinx))+10))))/(−1))=0

$$\underset{{x}\rightarrow\frac{\pi}{\mathrm{2}}} {\mathrm{lim}}\frac{−\mathrm{4cosx}−\frac{\frac{\mathrm{1}}{\mathrm{2}}.\frac{\mathrm{3}}{\sqrt{\mathrm{sinx}}}\mathrm{cosx}}{\sqrt{\mathrm{6}\sqrt{\mathrm{sinx}}+\mathrm{10}}}}{−\mathrm{1}}=\mathrm{0} \\ $$

Answered by mathmax by abdo last updated on 25/Jun/20

changement (π/2)−x =t give f(x)=((4sinx−(√(6(√(sinx))+10)))/((π/2)−x))  =((4cost −(√(6(√(cost))+10)))/t)=g(t)  we have cost ∼1−(t^2 /2) ⇒(√(cost))∼1−(t^2 /4) ⇒  6(√(cost))∼6−(3/2)t^2   ⇒(√(6(√(cost))+10))∼(√(16−(3/2)t^2 ))=4(√(1−((3t^2 )/(32))))∼4(1−((3t^2 )/(64))) ⇒  g(t) ∼((4−2t^2 −4+((3t^2 )/(16)))/t) =(−2+(3/(16)))t →0 ⇒lim_(x→(π/2))   f(x) =0

$$\mathrm{changement}\:\frac{\pi}{\mathrm{2}}−\mathrm{x}\:=\mathrm{t}\:\mathrm{give}\:\mathrm{f}\left(\mathrm{x}\right)=\frac{\mathrm{4sinx}−\sqrt{\mathrm{6}\sqrt{\mathrm{sinx}}+\mathrm{10}}}{\frac{\pi}{\mathrm{2}}−\mathrm{x}} \\ $$$$=\frac{\mathrm{4cost}\:−\sqrt{\mathrm{6}\sqrt{\mathrm{cost}}+\mathrm{10}}}{\mathrm{t}}=\mathrm{g}\left(\mathrm{t}\right)\:\:\mathrm{we}\:\mathrm{have}\:\mathrm{cost}\:\sim\mathrm{1}−\frac{\mathrm{t}^{\mathrm{2}} }{\mathrm{2}}\:\Rightarrow\sqrt{\mathrm{cost}}\sim\mathrm{1}−\frac{\mathrm{t}^{\mathrm{2}} }{\mathrm{4}}\:\Rightarrow \\ $$$$\mathrm{6}\sqrt{\mathrm{cost}}\sim\mathrm{6}−\frac{\mathrm{3}}{\mathrm{2}}\mathrm{t}^{\mathrm{2}} \:\:\Rightarrow\sqrt{\mathrm{6}\sqrt{\mathrm{cost}}+\mathrm{10}}\sim\sqrt{\mathrm{16}−\frac{\mathrm{3}}{\mathrm{2}}\mathrm{t}^{\mathrm{2}} }=\mathrm{4}\sqrt{\mathrm{1}−\frac{\mathrm{3t}^{\mathrm{2}} }{\mathrm{32}}}\sim\mathrm{4}\left(\mathrm{1}−\frac{\mathrm{3t}^{\mathrm{2}} }{\mathrm{64}}\right)\:\Rightarrow \\ $$$$\mathrm{g}\left(\mathrm{t}\right)\:\sim\frac{\mathrm{4}−\mathrm{2t}^{\mathrm{2}} −\mathrm{4}+\frac{\mathrm{3t}^{\mathrm{2}} }{\mathrm{16}}}{\mathrm{t}}\:=\left(−\mathrm{2}+\frac{\mathrm{3}}{\mathrm{16}}\right)\mathrm{t}\:\rightarrow\mathrm{0}\:\Rightarrow\mathrm{lim}_{\mathrm{x}\rightarrow\frac{\pi}{\mathrm{2}}} \:\:\mathrm{f}\left(\mathrm{x}\right)\:=\mathrm{0} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com